تقنية الكلام الجماعي (Arabic Choral Speaking) في تعليم مهارة الكلام - Nurrohmah, Latifah; Machmudah, Umi (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Speaking skill is important skills for mastering a language. When teaching the language, the teacher should use the correct and effective teaching technique in order to facilitate the students to learn and practice it. Focused the Arabic language lesson in MTsN 2 Magetan, learning vocabulary only. Film studied and practiced the speaking skill in the classroom because the students spoke Arabic difficulty. He must solve the problem, one of which is by using the kalam jamaie technique as a learning technique in teaching speaking skill. Students' activities when practicing the technique will help the students to practice speaking Arabic well. This research aims to find out the feasibility of using the kalam jamaie technique in teaching speaking skill at the MTsN 2 Magetan. I used method descriptive with a qualitative approach and a case study type in this research. I will use observation and documentation to collect data with the help of the research tool is the note sheet. The data in this research are the results of observation from the use of kalam jamaie technique, which is obtained from the data source is the students in the second grade (A) by 31 students. The sample taken from the research community is the students of the second grade with the amount of 198 students in the MTsN 2 Magetan. I will analyze the data with a descriptive analysis. The results of the research indicate that the feasibility of using the kalam jamaie technique to improve the speaking skill of students is “average”, because the students’ kalam jamaie technique is bad in the classroom, even if it is well-equipped and organized. This appears from the result of the observation on the use of kalam jamaie technique when applying the technique in the classroom.